Poder local, partido político e ditadura militar : a Aliança Renovadora Nacional (Arena) na Paraíba (1969-1979) - Dmitri da Silva Bichara Sobreira (2021)
This dissertation analyzes the Brazilian political party Aliança Renovadora Nacional (Arena), created in 1966, once the military dictatorship had extinguished other preexisting political acronyms in order to institute a two-party system. As part of such system, Arena’s function was one of support to the authoritarian regime, while Movimento Democrático Brasileiro (MDB) acted as the opposition, with the dictatorship’s consent. In this work, we focus our research on Arena’s performance in the state of Paraíba, having, as our chosen time frame, the period between 1969 and 1979 – the latter being the year when the party was extinct. Starting from an analysis of Paraíba’s Arena, we aim to understand the relationship between regional powers and the Brazilian dictatorship, as well as how the political system, assembled after the coup d’état in 1964, connected to the political class in the states, transiting between repression and a search for legitimation. We start from the perception of Arena as a vector of Brazil’s political culture, a perspective which helps us analyze the previous history of its members, how they understood and expressed their political perspectives, the reasons why they joined a party that served as the basis of an autocratic government which limited the operation of this same political class in several moments, and the way these members acted within it. By outlining our time frame as 1969-1979, we seek to observe how the local power reorganized itself after Institutional Act Number 5 (AI-5), a period when there was a series of purges against the political class, and when a project of party reorganization and renovation was proposed; to analyze the role of the governors, indirectly appointed by the federal government, in Paraíba, as well as the way they were chosen and the duties they performed as both representatives of the dictatorship in the states and leaders within Arena; to understand how Paraíba’s arenistas behaved as representatives of the civil society to the dictatorship; to delve into the conflicting relations between the existing political fractions within the party, and how these quarrels influenced the execution of the authoritarian modernization project elaborated by the Brazilian dictatorship.